Multimodal approach towards large area fully semitransparent perovskite solar module - Rai, Monika (2022)
Significant advancements in the perovskite solar cells/modules (PSCs/PSMs) toward better operational stability and large area scalability have recently been reported. However, semitransparent (ST), high efficiency, and large area PSMs are still not well explored and require attention to realize their application in building-integrated photovoltaics (BIPV). This work employs multiple synergistic strategies to improve the quality and stability of the ST perovskite film while ensuring high transparency. Europium ions, doped in the perovskite, are found to suppress the generation of detrimental species like elemental Pb and I, resulting in higher atmospheric stability. The effect of the top transparent contact is designed to obtain an average visible transparency (AVT) of >20% for full device and a green colored hue. Lastly, the lower current density due to the thinner ST absorber is enhanced by the application of a down-converting phosphor material which harvests low energy photons and inhibits UV-induced degradation. This multimodal approach renders a power conversion efficiency of 12% under dim light conditions and 9.5% under 1 sun illumination, respectively, on 21 cm2 ST-PSM.